2015
DOI: 10.1177/1742395315574765
|View full text |Cite
|
Sign up to set email alerts
|

Needs of caregivers in heart failure management: A qualitative study

Abstract: ObjectivesTo identify the needs of caregivers supporting a person with heart failure and to inform the development of a caregiver resource to be used as part of a home-based self-management programme.MethodsA qualitative study informed by thematic analysis involving 26 caregivers in individual interviews or a focus group.ResultsThree distinct aspects of caregiver support in heart failure management were identified. Firstly, caregivers identified needs about supporting management of heart failure including: cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
92
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(108 citation statements)
references
References 28 publications
6
92
1
9
Order By: Relevance
“…Qualitative studies [30, 36, 40, 42, 45, 48, 54, 61, 71, 72, 74, 77, 80, 83, 88, 104, 110, 117, 119, 131, 137, 138, 142] described a wide range of needs that caregivers felt underprepared for or in need of assistance with, including coping with and managing symptoms; understanding HF and prognosis; handling unplanned hospitalizations and other emergencies; managing medications and devices; providing and receiving emotional and spiritual support; partnering in patients’ self-care; balancing home and work; engaging in their own self-care; having difficult conversations; handing uncertainty about the future and the unpredictably of the disease; communication and care coordination; understanding palliative care services; managing the home; dealing with financial issues; knowing what to expect and how to care for patients at end of life; and leveraging and timely access to formal and informal social support and services. Two quantitative studies both identified handling emergencies as a situation that caregivers’ felt most unprepared for [127, 136].…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative studies [30, 36, 40, 42, 45, 48, 54, 61, 71, 72, 74, 77, 80, 83, 88, 104, 110, 117, 119, 131, 137, 138, 142] described a wide range of needs that caregivers felt underprepared for or in need of assistance with, including coping with and managing symptoms; understanding HF and prognosis; handling unplanned hospitalizations and other emergencies; managing medications and devices; providing and receiving emotional and spiritual support; partnering in patients’ self-care; balancing home and work; engaging in their own self-care; having difficult conversations; handing uncertainty about the future and the unpredictably of the disease; communication and care coordination; understanding palliative care services; managing the home; dealing with financial issues; knowing what to expect and how to care for patients at end of life; and leveraging and timely access to formal and informal social support and services. Two quantitative studies both identified handling emergencies as a situation that caregivers’ felt most unprepared for [127, 136].…”
Section: Resultsmentioning
confidence: 99%
“…Such knowledge would enable pharmacy staff to offer more extensive carer support, such as signposting carers to external organisations. Other research has demonstrated that carers may not know which services are available to them [27][28][29] and that pharmacists can fulfil an important role as information providers and/ or care coordinators. [30] Participants emphasised that information on key support organisations such as Carers Australia was underutilised in practice and that they only became aware of these agencies following training in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns or issues about managing medication, as evidenced by the extensive literature available on this topic (Alhaddad, Taylor, Robertson, Watman, & Smith, ; Look & Stone, ; Maidment et al, ; Wingham et al, ), was noticeably absent from our data. This was surprising given that pharmacists are well placed to address medication‐related issues.…”
Section: Discussionmentioning
confidence: 64%